Environmental colour impact upon human behaviour: a review - Ab Jalil, Nurlelawati; Mohd Yunus, Rodzyah; Sheik Said, Normahdiah (Elsevier, 2012)
This paper analyses 40 previous colour studies selected from various disciplines discussing previous methods and colour effects in order to find its significant impact on humans. It reviews factors such as type of setting, method of assessment, instruments and type of colours. Secondly, it discuss how colours or coloured environment have influence working performances; causing certain behavior; creating negative or positive perception to surroundings and task given; and influencing moods and emotions. Finally, this paper highlights the potential scientific approach in finding colour effects on human behaviour. The paper summarized factors to be included for further steps of current investigation.